Acute effects of whole body vibration combined with blood restriction on electromyography amplitude and hormonal - Cai, Z. Y.; Chen, W. C.; Wu, C. M. (Biology of Sport, 2018)
The purpose of this study was to investigate the effects of whole body vibration (WBV) exercise with and without blood flow restriction (BFR) on electromyography (EMG) amplitude and hormonal responses. Eight healthy male adults who lacked physical activity participated in this study and completed 10 sets of WBV and WBV + BFR sessions in a repeated measures crossover design. In the WBV + BFR session, the participants wore a BFR device inflated to 140 mmHg around the proximal region of the thigh muscles. The results indicated that the EMG values from the rectus femoris and vastus lateralis during the WBV + BFR session were significantly higher than those during the WBV session (p < 0.05). Two-way analysis of variance with repeated measures showed that the WBV + BFR and WBV exercise sessions induced a significant (simple main effect for time) increase in lactate (LA) (0.61-4.68 vs. 0.46-3.44 mmol/L) and growth hormone (GH) (0.48-3.85 vs. 0.47-0.82 ng/mL) responses after some of the post-exercise time points (p < 0.05). WBV + BFR elicited significantly higher LA and GH (simple main effect for trial) responses than did WBV after exercise (p < 0.05). Although no significant time × trial interactions were observed for testosterone (T) (604.5-677.75 vs. 545.75-593.88 ng/dL), main effects for trial (p < 0.05) and for time (p < 0.05) were observed. In conclusion, WBV + BFR produced an additive effect of exercise on EMG amplitude and LA and GH responses, but it did not further induce T responses compared to those with WBV alone.